ANALISIS KESALAHAN TUTURAN CALON WAITER/WAITRESS PADA AGEN KAPAL PESIAR PT. BPC DITINJAU DARI KATEGORI STRATEGI PERFORMASI, TAKSONOMI KOMPARATIF DAN KATEGORI EFEK KOMUNIKASI - Sukra, I Nyoman (Jurnal Ekonomi dan Pariwisata, 2017)
Abstract The research of an analysis of error made by the candidate of cruise ship waiter and waitress during their communication with the guests from the performation strategy category, comparative taxonomy and communication effect category point of view is a descriptive research. This research aims at finding out the types, the cause and the effects of the error toward the communication process. The result of this research indicated that the candidate of cruise ship waiter and waitress made two kinds of error: 1) Performative category such as addition, omission, misformation and misordering. 2) Comparative category such as interlingual, intralingual and ambigue. Those errors are as the result of lack understanding of the English Language principles and the intervention of the first language as well. Key words: error, communication, performation, comparative.